At the Dawn of Legal History: Teaching Law in Ancient Mesopotamia - Fijałkowska, Lena (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The article presents an outline of legal teaching in ancient Mesopotamia, with emphasis on the available sources and the difficulties they present. Though our knowledge of this topic is still fragmentary, for several periods the scribal curriculum can be reconstructed, as well as the place of legal education therein. The innate conservatism of Mesopotamian culture notwithstanding, it turns out that the latter managed to produce surprisingly skilled and creative legal professionals.